2017
DOI: 10.1177/1049909117730024
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in End-of-Life Decisions for Newborns in a Korean Hospital

Abstract: In Korea, changes in the decisions on end-of-life care in neonates are shifting from active resuscitation to nonactive resuscitation based on clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…It has been reported that guardians withholding or withdrawing intensive care for extremely preterm infants at the limits of viability has become more acceptable than it was 20 years ago in Germany, Switzerland, and Austria [18]. The incidence of withdrawing treatment in recent years in this study is similar to the incidence of withdrawing treatment of neonatal intensive care in Korea [19]. The frequency of PICU patients who undergo the process of withholding or withdrawing life-sustaining treatment was 1.5% in Chile from 2004 to 2014 [20].…”
Section: Definition Of Withdrawing Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been reported that guardians withholding or withdrawing intensive care for extremely preterm infants at the limits of viability has become more acceptable than it was 20 years ago in Germany, Switzerland, and Austria [18]. The incidence of withdrawing treatment in recent years in this study is similar to the incidence of withdrawing treatment of neonatal intensive care in Korea [19]. The frequency of PICU patients who undergo the process of withholding or withdrawing life-sustaining treatment was 1.5% in Chile from 2004 to 2014 [20].…”
Section: Definition Of Withdrawing Treatmentsupporting
confidence: 62%
“…The frequency of PICU patients who undergo the process of withholding or withdrawing life-sustaining treatment was 1.5% in Chile from 2004 to 2014 [20]. Decisions on end-of-life care in neonates shifted from active resuscitation to non-active resuscitation in Korea between 2001 and 2015 [19]. In contrast, the proportion of non-active resuscitation for critically ill children in China is declining.…”
Section: Definition Of Withdrawing Treatmentmentioning
confidence: 99%
“…Decisions on end-of-life care for neonates shifted from active resuscitation to non-active resuscitation in Korea between 2001 and 2015 [31]. In contrast, the proportion of cases of non-active resuscitation for critically ill children in China is declining.…”
Section: Discussionmentioning
confidence: 99%
“…Decisions on end-of-life care in neonates shifted from active resuscitation to non-active resuscitation in Korea between 2001 and 2015 [31]. In contrast, the proportion of cases of non-active resuscitation for critically ill children in China is declining.…”
Section: Discussionmentioning
confidence: 99%